2011
DOI: 10.1016/j.ijgo.2010.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Early‐onset severe growth restriction and placental abruption associated with Breus mole

Abstract: An 18-year-old primigravida with raised α-fetoprotein levels at 15 weeks of pregnancy displayed reduced amniotic fluid volume (amniotic fluid index [AFI], 11 cm) and bulky placenta at her 20-week mid-trimester scan.A repeat scan at 24 + 6 weeks showed reduced AFI (13 cm), absent end diastolic flow, bulky placenta, and no fetal growth-with significant asymmetric growth restriction (estimated fetal weight, 341 g) (Fig. 1). Because of early-onset severe growth restriction and absent end diastolic flow, the woman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Kojima Secondly, although the original description was in a nonviable pregnancy, 11 a combined survival rate of 50% (6/12 cases) is evident in a series of previous case reports. [12][13][14][15][16][17][18] Our relatively large single center experience demonstrating a 50% survival is consistent with the cumulative experience of the earlier reports. Although subject to ascertainment bias, our data demonstrate that survival is possible with this condition.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Kojima Secondly, although the original description was in a nonviable pregnancy, 11 a combined survival rate of 50% (6/12 cases) is evident in a series of previous case reports. [12][13][14][15][16][17][18] Our relatively large single center experience demonstrating a 50% survival is consistent with the cumulative experience of the earlier reports. Although subject to ascertainment bias, our data demonstrate that survival is possible with this condition.…”
Section: Discussionsupporting
confidence: 84%
“…Most descriptions of the ultrasound appearances of Breus' mole, also referred to as massive subchorionic thrombohematoma (MTH), have been in case reports . In contrast with the original description in a nonviable pregnancy, a later report demonstrated that fetal survival may be possible with this condition .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…29 A case report describing severe growth restriction and abnormal umbilical artery Doppler studies at 24 weeks' gestation in the setting of an SCH reported a placental abruption and fetal demise at 25 weeks' gestation. 34 In the meta-analysis by Tuuli et al, 6 SCH had an OR of 5.71 (CI, 3.91-8.33) for abruption.…”
Section: Placental Abruptionmentioning
confidence: 98%
“…33 Fetal growth restriction and absent end diastolic flow on umbilical artery Doppler studies at 24 6/7 weeks' gestation in the setting of a massive SCH have also been described. 34 In a series of massive SCHs, 10/17 patients had FGR, and 5 also had abnormal umbilical artery Doppler studies (absent or reversed end diastolic flow). 29 All 5 fetuses that had abnormal umbilical artery Doppler studies ended with a fetal demise.…”
Section: Fetal Growth Restrictionmentioning
confidence: 99%